2021
DOI: 10.3390/jcm10143039
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility to Acute Kidney Injury

Abstract: Acute kidney injury (AKI) is a widely held concern related to a substantial burden of morbidity, mortality and expenditure in the healthcare system. AKI is not a simple illness but a complex conglomeration of syndromes that often occurs as part of other syndromes in its wide clinical spectrum of the disease. Genetic factors have been suggested as potentially responsible for its susceptibility and severity. As there is no current cure nor an effective treatment other than generally accepted supportive measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 144 publications
0
15
0
Order By: Relevance
“…Diabetes increases the risk of acute kidney injury (AKI), which can sometimes be regarded as an acute complication of diabetes [4]. AKI is a sudden renal dysfunction syndrome with a high incidence rate and mortality, is common in patients with critical illness and cardiac surgery and is associated with genetic susceptibilities [5][6][7]. Studies have found that AKI affects more than 13 million people per year, 80% of patients live in the developing world, and AKI contributes to 1.7 million deaths annually [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes increases the risk of acute kidney injury (AKI), which can sometimes be regarded as an acute complication of diabetes [4]. AKI is a sudden renal dysfunction syndrome with a high incidence rate and mortality, is common in patients with critical illness and cardiac surgery and is associated with genetic susceptibilities [5][6][7]. Studies have found that AKI affects more than 13 million people per year, 80% of patients live in the developing world, and AKI contributes to 1.7 million deaths annually [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the rodents are basically genetically identical or inbred animals in AKI in order to reduce experimental influence factors and improve data stability [ 248 ]. Patients with AKI have high diverse genetic diversity [ [249] , [250] , [251] ], which may affect the efficacy of nanodrugs. Moreover, current animal models of AKI do not reflect the complete characteristics of clinical AKI patients.…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…A number of studies have suggested the role of genetic polymorphisms in the development of CSA-AKI. Polymorphisms of angiotensinogen, apolipoprotein E (APOE), angiotensin-converting enzyme (ACE), endothelial nitric oxide synthase (eNOS), erythropoietin, interleukin-6 (IL-6), interleukin-10 (IL-10), catechol-O-methyltransferase (COMT), GRM7 | LMCD1—AS1 loci and BBS9, transducer and activator of transcription 3 (STAT3), and macrophage migration inhibitory factor (MIF) genes have been proven to be associated with a higher risk of AKI after cardiac surgery [ 100 ]. However, some studies have denied a correlation between some of these gene polymorphisms and CSA-AKI [ 101 , 102 ].…”
Section: Theories Of Csa-aki Pathophysiologymentioning
confidence: 99%